Antibacterial surface treatment for orthopaedic implants - Gallo, Jiri; Holinka, Martin; Moucha, Calin S (International journal of molecular sciences, 2014)
It is expected that the projected increased usage of implantable devices in medicine will result in a natural rise in the number of infections related to these cases. Some patients are unable to autonomously prevent formation of biofilm on implant surfaces. Suppression of the local peri-implant immune response is an important contributory factor. Substantial avascular scar tissue encountered during revision joint replacement surgery places these cases at an especially high risk of periprosthetic joint infection. A critical pathogenic event in the process of biofilm formation is bacterial adhesion. Prevention of biomaterial-associated infections should be concurrently focused on at least two targets: inhibition of biofilm formation and minimizing local immune response suppression. Current knowledge of antimicrobial surface treatments suitable for prevention of prosthetic joint infection is reviewed. Several surface treatment modalities have been proposed. Minimizing bacterial adhesion, biofilm formation inhibition, and bactericidal approaches are discussed. The ultimate anti-infective surface should be "smart" and responsive to even the lowest bacterial load. While research in this field is promising, there appears to be a great discrepancy between proposed and clinically implemented strategies, and there is urgent need for translational science focusing on this topic.
Keywords: ortopedie; povrchové vlastnosti; Surface Properties; Prosthesis-Related Infections; Coated Materials, Biocompatible; Anti-Bacterial Agents; biokompatibilní potahované materiály; Humans; Prostheses and Implants; Orthopedics; infekce spojené s protézou; Bacteria; lidé; antibakteriální látky; protézy a implantáty